Crushing of additively manufactured thin-walled metallic lattices: Two-scale strain localization analysis. (September 2021) - Balit, Yanis; Margerit, Pierre; Charkaluk, Eric; Constantinescu, Andrei
Abstract: The response of architectured structures is characterized by multi-scale kinematics, which complex relation and effect on the engineering load response is still not completely understood and therefore needs further investigations. More precisely, the lack of experimental methods enabling to provide multi-scale data remains a key issue. The paper presents an experimental and numerical analysis of crushing tests performed on thin-walled auxetic metallic lattices manufactured by Directed Energy Deposition. The work is focused on the two-scale strain localization occurring (a) at the microscopic scale of the unit cell and (b) at the macroscopic scale corresponding to the homogenized continuum. The structures of interest are defined as the extrusion of a 2D auxetic wireframe and allow the application of an adapted digital image correlation scheme dedicated to the identification of the kinematics at the two considered scales. In particular, the microscopic kinematics are studied by following the deformation of lattice crossings, while the macroscopic strains are deduced from the motion of virtual unit cell corners. The results show that the global elastic-plastic response of the lattices is completely driven by the formation of plastic hinges at specific locations, leading to characteristic deformation patterns and eventually a collective behavior of neighboring unit cells. Companion finite element computations show an excellent match with experiments and thus enable to assess the effect of modeling assumptions, unit cell geometry, strain rate and geometrical imperfections in the global response of the architecture material. Graphical abstract: Image 1 Highlights: Experimental investigation of the crushing behavior of lattices manufactured by Directed Energy Deposition. Micro and macro structural kinematics are identified by tracking unit cell features. Strain localizations occurring at both scales drive the global mechanical response. Influence of unit cell geometry and defects assessed by a companion FE model.